May solid food refusal and other non-specific neurological symptoms be an early symptoms of Vitamin B12 deficiency in complementary feeding period? (Annals of Medical Research, 2021)
Aim: In this study, we showed an early symptoms of VB12 deficiency in infancy complementary feeding period (CFP) without hematologic findings. Vitamin B-12 (VB12) deficiency can result in severe neurological degeneration within the first year of life. In literature, symptoms of VB12 deficiency in infant were described with hematologic findings which were like a pernicious anemia. Material and Methods: A 104 of 1,848 mother-infant pairs admitted for well-child visits between January 2018 and December 2018 were included in the study. All babies were diagnosed with vitamin B12 deficiency. All baby-mother pairs were monitored during the CFP were included in the study. Overall, 83 mother who met the inclusion criteria and who agreed to participate in the study and their babies, were included in the study.Results: The cause of follow-up of these children was refusal to breastfeed and irritability in 21 infants (25.3%). There were 19 infants (22.9%) with solid food refusal, 16 infants (19.2%) with sleeping problems, and 16 infants (19.2%) with failure to thrive. In the remaining 11 infants (13.2%), there were mild hypotonia, microcephalia, vomiting, and growth retardation. The mean age for the development of these symptoms was 5.5 ± 1.7 months, while the mean age of being diagnosed with VB12 deficiency was 6.4±1.2 months. Conclusions: In this study, symptoms of VB12 deficiency without any hematological symptoms and not caused by other organic causes, and arising during the period of transition to complementary feeding, were demonstrated. Physician must be aware of early findings of VB12 deficiency before severe neurological findings and hematological sypmtoms.
Keywords: Breastfeeding; deficiency; vitamin B12